2017
DOI: 10.19082/3862
|View full text |Cite
|
Sign up to set email alerts
|

Development of the UTAUT2 model to measure the acceptance of medical laboratory portals by patients in Shiraz

Abstract: IntroductionOne of the main stages for achieving the success is acceptance of technology by its users. Hence, identifying the effective factors in successful acceptance of information technology is necessary and vital. One such factor is usability. This study aimed to investigate the software usability in the “Unified Theory of Acceptance and Use of Technology 2 (UTAUT2)” model in patients’ use of medical diagnosis laboratories’ electronic portals in 2015.MethodsThis cross-sectional study was carried out on 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 37 publications
9
18
0
2
Order By: Relevance
“…Our result is similar to the findings of Ravangard et al (2017) and Albugami and Bellaaj (2014). It is recommended that the quality of the website needs to be maintained in high standards in order to give faith to the students to use it more.…”
Section: Resultssupporting
confidence: 93%
“…Our result is similar to the findings of Ravangard et al (2017) and Albugami and Bellaaj (2014). It is recommended that the quality of the website needs to be maintained in high standards in order to give faith to the students to use it more.…”
Section: Resultssupporting
confidence: 93%
“…Hence, price value can serve as a behavioural intention predictor for mobile Internet adoption. Price value also shows a significant impact on intention to use (Ravangard et al, 2017).…”
Section: Price Valuementioning
confidence: 98%
“…The actual usage of a technology occurs when a person intends to use it. Evidence showed that behavioral intention has a direct impact on actual usage of technology (26,30,36).…”
Section: Behavioral Intention (Bi)mentioning
confidence: 99%
“…, Hoque and Sorwar (2017) (28), Hsu and Hsieh, (2017) (47), and Ravangard et al (2017)(36). Behavioral intention predicts the actual usage of BL.…”
mentioning
confidence: 97%